2009
DOI: 10.1007/s00128-009-9917-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Estrogenic Activity from Kraft Mill Effluents by the Yeast Estrogen Screen

Abstract: Estrogenic activity of kraft pulp mill effluents (P. radiata, E. globulus and mixed -50% E. globulus and 50% P. radiata) was evaluated by the yeast estrogen screen assay. The estrogenic activity values were relatively low, ranking between 1.475 and 0.383 ng/L of EE2 eq. (Estrogenic equivalent of 17 alpha-ethynylestradiol), where the highest value corresponds to the E. globulus effluent and the lowest value to the P. radiata effluent. Analysis by solid phase extraction (SPE) and gas chromatography-mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…Although not native to or used medicinally in Africa, Eucalyptus grandis is an important fuel wood species there and an important source of paper products throughout the world. Studies of mill effluents have shown a related species, E. globulus , to have estrogenic activity, and this is suggested to relate to the feminization of male fish living downstream from such factories (Chamorro etal.,2010). Considering that E. grandis is a nonnative tree species growing along the edges of both KNP and BINP, and that numerous primate species, including black‐and‐white colobus monkeys ( Colobus guereza ), (Harris and Chapman,2007), mountain gorillas (Rothman et al,2006b), red colobus monkeys (MW, personal observation ), and Guatemalan black howler monkeys ( Alouatta pigra ) (Bonilla‐Sanchez et al, 2012), are thought to seek it out for its high sodium content (Rode et al,2003; Rothman et al,2006b), future studies should examine the possibility that E. grandis may act as a source of endocrine disruption for primates.…”
Section: Discussionmentioning
confidence: 99%
“…Although not native to or used medicinally in Africa, Eucalyptus grandis is an important fuel wood species there and an important source of paper products throughout the world. Studies of mill effluents have shown a related species, E. globulus , to have estrogenic activity, and this is suggested to relate to the feminization of male fish living downstream from such factories (Chamorro etal.,2010). Considering that E. grandis is a nonnative tree species growing along the edges of both KNP and BINP, and that numerous primate species, including black‐and‐white colobus monkeys ( Colobus guereza ), (Harris and Chapman,2007), mountain gorillas (Rothman et al,2006b), red colobus monkeys (MW, personal observation ), and Guatemalan black howler monkeys ( Alouatta pigra ) (Bonilla‐Sanchez et al, 2012), are thought to seek it out for its high sodium content (Rode et al,2003; Rothman et al,2006b), future studies should examine the possibility that E. grandis may act as a source of endocrine disruption for primates.…”
Section: Discussionmentioning
confidence: 99%
“…Effluent discharges from the kraft pulp mill have been identified as a potential contaminant of aquatic environments (Belmonte et al 2006;Vidal et al 2007;Chamorro et al 2010). Their compound nature is derived from the presence of several naturally occurring and xenobiotic compounds, which are formed and released during various stages of the process .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Investigations carried out intended to recognize its real dimension are scarce but in constant development. 2,7 This kind of compounds can cause physiological abnormalities 1,5,8 or even morphological. 3 Orrego et al 7,9 stated an increased size and precocious gonad maturity in females as well as an increase in the plasmatic vitelogenine in juvenile males of Oncorhynchus mykiss exposed to sediments influenced by effluents derived from the cellulose production in the Biobío River.…”
Section: Introductionmentioning
confidence: 99%
“…1 The generation of effluents from the production of cellulose, affects mainly to the Central Southern zone, in the Biobío basin region and have identified as a potential source of endocrinal activity in the receiving water bodies [2][3][4] due to the presence, among others, of wood extractives such as fatty acids, sterols, phenolic compounds and terpenes (di and triterpenes are emphasized). 5,6 Investigations carried out intended to recognize its real dimension are scarce but in constant development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation